Qualitative Analysis of a Twitter-Disseminated Survey Reveals New Patient Perspectives on the Impact of Urinary Tract Infection - Marissa Valentine-King; Lindsey Laytner; Casey Hines-Munson; Kiara Olmeda; Barbara Trautner; Sheryl Justice; Christina Ching; Larissa Grigoryan (MDPI AG, 2022)
Few studies have harnessed social media to explore patients' experiences with urinary tract infection (UTI); therefore, we captured UTI experiences and future research suggestions through a Twitter-disseminated survey. The survey posed three qualitative questions inquiring about the impact of UTIs, greatest UTI management hurdle, and research suggestions. We also asked participants to rate how seriously others perceive UTIs and the importance of UTIs in their life (scale: 1-100 (highest)). The study period spanned from January to June 2021. Coding was performed in duplicate, followed by thematic analysis. Of 466 participants from 22 countries, 128 considered their UTIs recurrent (n = 43) or chronic (n = 85). Six major themes emerged: UTIs drastically impact (1) physical and (2) mental health and (3) cause severe limitations in life activities. Patients reported (4) negative clinician interactions and perceived inadequate care, (5) a lack of knowledge and awareness surrounding UTIs, and (6) research gaps in UTI diagnostics and treatment. The participants considered UTIs extremely important (median: 100, IQR: 90-100), but characterized others' perceptions of them as less serious (median: 20, IQR: 10-30). Our survey revealed a patient population struggling with UTIs, particularly chronic UTIs. Our findings highlight perceived shortcomings in current UTI treatment and diagnostics.